Apol9a regulates myogenic differentiation via the ERK1/2 pathway in C2C12 cells - Jiang, Xuan; Ji, Siyu; Cui, Siyuan; Wang, Rong; Wang, Wei; Chen, Yongquan; Zhu, Shenglong (Frontiers in Pharmacology, 2022)
Abstract Background The rising prevalence of obesity and its complications is a big challenge for the global public health. Obesity is accompanied by biological dysfunction of skeletal muscle and the development of muscle atrophy. The deep knowledge of key molecular mechanisms underlying myogenic differentiation is crucial for discovering novel targets for the treatment of obesity and obesity-related muscle atrophy. However, no effective target is currently known for obesity-induced skeletal muscle atrophy. Methods Transcriptomic analyses were performed to identify genes associated with the regulation of myogenic differentiation and their potential mechanisms of action. C2C12 cells were used to assess the myogenic effect of Apol9a through immunocytochemistry, western blotting, quantitative polymerase chain reaction, RNA interference or overexpression, and lipidomics. Results RNA-seq of differentiated and undifferentiated C2C12 cells revealed that Apol9a expression significantly increased following myogenic differentiation and decreased during obesity-induced muscle atrophy. Apol9a silencing in these C2C12 cells suppressed the expression of myogenesis-related genes and reduced the accumulation of intracellular triglycerides. Furthermore, RNA-seq and western blot results suggest that Apol9a regulates myogenic differentiation through the activation of extracellular signal-regulated kinase 1/2 (ERK1/2). This assumption was subsequently confirmed by intervention with PD98059. Conclusions In this study, we found that Apol9a regulates myogenic differentiation via the ERK1/2 pathway. These results broaden the putative function of Apol9a during myogenic differentiation and provide a promising therapeutic target for intervention in obesity and obesity-induced muscle atrophy.